2009
DOI: 10.3171/2008.6.17605
|View full text |Cite
|
Sign up to set email alerts
|

Significant reduction in stereotactic and functional neurosurgical hardware infection after local neomycin/polymyxin application

Abstract: Pain relief after MVD is strongly correlated with the lancinating pain component, and therefore type of TN pain is the best predictor of long-term outcome after MVD. Application of this information should be helpful in the selection of TN patients likely to benefit from MVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 32 publications
2
52
1
Order By: Relevance
“…In a large cohort of neurosurgical patients undergoing implantation of hardware, the infection rate was lowest (effectively zero) in those treated with local neomycin/polymixin treatment in addition to systemic antibiotics. 63 The old adage that "the solution to pollution is dilution" may hold true, although caveats exist. Local wound irrigation, particularly with detergent additives, is effective at cleansing surgical wounds.…”
Section: Antibiotic Administrationmentioning
confidence: 99%
“…In a large cohort of neurosurgical patients undergoing implantation of hardware, the infection rate was lowest (effectively zero) in those treated with local neomycin/polymixin treatment in addition to systemic antibiotics. 63 The old adage that "the solution to pollution is dilution" may hold true, although caveats exist. Local wound irrigation, particularly with detergent additives, is effective at cleansing surgical wounds.…”
Section: Antibiotic Administrationmentioning
confidence: 99%
“…An infection caused by DBS hardware is one of the most serious complications [1,2,5,6,7,8], with the incidence of reported DBS-related infections ranging widely between 1.2 and 23% [1,2,3,4,8,9,10,11,12]. Although many patients with lead or internal pulse generator (IPG) pocket-associated DBS infection require device removal for clinical cure, accurate diagnosis and management of the infection may avoid the morbidity caused by DBS removal when the infection is not confirmed or is medically cured [1].…”
Section: Introductionmentioning
confidence: 99%
“…2 In one of the few neurosurgical publications on this topic, Miller et al reported that local neomycin and polymyxin combined with systemic antibiotics were superior to systemic antibiotics alone in reducing stereotactic and functional hardware infection, with no associated complications. 27 We found the use of bacitracin powder to be economical and safe. The typical uses of bacitracin as a dilute wound irrigant during surgery and as a topical ointment applied to the skin have been associated with relatively few serious complications.…”
mentioning
confidence: 99%
“…Miller et al showed that the infusion of concentrated neomycin and polymyxin directly into wounds during deep brain stimulator implantation resulted in a 1.2% infection rate, which was significantly lower than the 5.7% rate reported in their historical cohort in which concentrated antibiotics were not instilled just prior to closure. 27 In this study, we evaluated the association between concentrated bacitracin powder applied directly to wounds prior to closure during cranial shunt surgery and shunt infection in a large children's hospital. We believe this is the first published report to study the effect of the direct application of a concentrated antibiotic powder to surgical wounds during cranial shunt surgery.…”
mentioning
confidence: 99%